LOVE AS THE ESSENTIAL EXPRESSION OF HUMAN ONTOLOGY (D. VON HILDEBRAND, M. SHELER, E. FROMM) - Климань, С. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The paper reveals the problem of love as a phenomenon of transcendence, that brings a person to a new level of understanding of himself as a «whole person». The feasibility of the understanding of love as the essential beginning of the ontology of man as an existential response to the problematic issues of human existence can be proved by analyzing the works D. Hildebrand, M. Scheler, E. Fromm.